1. Limited time only! Sign up for a free 30min personal tutor trial with Chegg Tutors
    Dismiss Notice
Dismiss Notice
Join Physics Forums Today!
The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

Homework Help: Max, Min

  1. Feb 26, 2009 #1
    1. The problem statement, all variables and given/known data

    (a) Let f,g: [a,b] [tex]\rightarrow[/tex] [tex]\Re[/tex].

    Define: f [tex]\vee[/tex] g(x) = max(f(x),g(x)), x[tex]\in[/tex] [a,b]
    f [tex]\wedge[/tex] g(x) = min(f(x),g(x)), x[tex]\in[/tex] [a,b]

    (b) Let [tex]f_{+}[/tex] = f[tex]\vee[/tex]0, [tex]f_{-}[/tex] = -(f[tex]\wedge[/tex]0)
    Show that: f = [tex]f_{+}[/tex] - [tex]f_{-}[/tex]
    abs value of f = [tex]f_{+}[/tex] + [tex]f_{-}[/tex]

    2. Relevant equations

    [tex]f_{+}[/tex], [tex]f_{-}[/tex] [tex]\geq[/tex] 0

    3. The attempt at a solution

    (a) f [tex]\vee[/tex] g(x) equals the supremum and infimum for f [tex]\wedge[/tex] g(x). Supremum would be "b" for both f and g, and infimum of both would be "a"??

    (b) Lost with this one. It relates to the first question I know, but trying to put them together hasn't been working.
  2. jcsd
  3. Feb 27, 2009 #2


    User Avatar
    Science Advisor

    NO, of course not. a and b are the smallest and largest values of x. Your functions are defined as inf and sup of f(x) and g(x), the function values.
    What exactly are you trying to do here? In (a) you are given two definitions but I see no question!

    Again, what was the first question? What is f+- f- and f++ f- for individual values of x? Try looking at specific f and g functions. Suppose f(x)= 2x, g(x)= x. What are f+ and f-?
  4. Feb 27, 2009 #3
    yep, definately wrote it wrong, (a) was what was given, thought it was a question.

    the question was something like this: using what was given, graph each of the following on the given axis, f(x),g(x), f [tex]\wedge[/tex]
    g, f [tex]\vee[/tex] g:
    f(x)=sinx, g(x)=cosx, x in [0,2pi] and graph f(x)=x(x-1)(x-2)(x-3), g(x)=0, x in [0,3]

    and then (b) above was correct, using what was defined show that
    Last edited: Feb 27, 2009
Share this great discussion with others via Reddit, Google+, Twitter, or Facebook